Growth temperature dependence of VLS-grown ultra-long ZnS nanowires prepared by CVD method - Mohammad Reza Khanlary; Shima alijarahi; Ali Reyhani (Journal of Theoretical and Applied Physics)
Abstract The synthesis of ultra-long high-quality zinc sulfide (ZnS) nanowires of uniform size on heterogeneous substrates is highly desirable for investigating the fundamental properties of ZnS nanowires and for fabricating integrated functional nanodevices. The present study developed a novel technique for growing ultra-long ZnS nanowires on thin-catalyst-coated substrates. ZnS nanowires were synthesized by chemical vapor deposition on a silicon substrate deposited by gold (~ 5 nm in thickness) as the catalyst at 550, 600, 700, 750 and 800 °C. The structural properties of the samples were investigated by X-ray diffraction, and the results showed that the fabricated nanowires have both wurtzite and zinc blend structures. The morphological properties of the nanowires were determined by scanning electron microscopy, and the results show that the substrate is thoroughly coated with 10 µm of zinc sulfide nanowires. Increasing the substrate temperature from 600 to 800 °C increased the diameter of the nanowires and decreased the length. The growth mechanism of the nanowires was vapor–liquid–solid. The EDX spectra of this sample showed an absence of contamination, confirming the high purity of the ZnS nanowires.